1997
DOI: 10.1051/jp4:1997547
|View full text |Cite
|
Sign up to set email alerts
|

Martensitic Transformations in TiNi Alloys with Ti3Ni4 Precipitates

Abstract: Abstract. The thermoelastic martensitic transformations in Ti 4 .>Ni5, and Ti 48 Nij2 alloys after isothermal aging have been studied by means of transmission electron microscopy and dilatometry. The presence of TUNi 4 precipitates and the difference in precipitates size affect the martensite nucleation and martensitic transformation temperatures and sequences in TiNi alloys. Highly coherent and densely dispersed TUNi 4 particles (<20-50 nm length) after initial aging stages depresses B2-»B19' transition and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…The conclusions concerning the phase composi tion and martensitic transformations that occur in the alloy after aging agree with the results of [22,23]. It has been shown in these works that the aging of the alloys with a relatively small excess of nickel concentration over the equiatomic concentration (50.6% Ni) in the temperature range of 400-500°C leads to the precipi tation of Ni 4 Ti 3 particles at grain boundaries and near them, whereas part of the volume inside grains remains free of these precipitates.…”
Section: Martensitic Transformations and Phase Composition After Agingsupporting
confidence: 83%
See 1 more Smart Citation
“…The conclusions concerning the phase composi tion and martensitic transformations that occur in the alloy after aging agree with the results of [22,23]. It has been shown in these works that the aging of the alloys with a relatively small excess of nickel concentration over the equiatomic concentration (50.6% Ni) in the temperature range of 400-500°C leads to the precipi tation of Ni 4 Ti 3 particles at grain boundaries and near them, whereas part of the volume inside grains remains free of these precipitates.…”
Section: Martensitic Transformations and Phase Composition After Agingsupporting
confidence: 83%
“…The presence of three stages of the forward martensitic transformation along with the time-temperature regime of aging give grounds to conclude that, apart from two types of martensite, the phase composition of the samples of the alloy under investigation also included precipitates of Ni 4 Ti 3 . According to [22][23][24][25], the nonuniformity of the distri bution of these precipitates in the microstructure is the reason for the multistage martensitic transformations in the aged NiTi alloys. Based on the results of previ ous investigations [22,26,27] and on the regime of aging used in this work, we can assume that the volume fraction of these precipitates in the samples of our alloy was about 2% and that their size and spacings between them were equal to approximately 100-200 nm.…”
Section: Martensitic Transformations and Phase Composition After Agingmentioning
confidence: 99%
“…They attributed, as other authors [6], the suppression of the B2-B19 0 MT to the early stage of the formation of precipitates and suggested that such precipitation can occur during quenching the samples from 1270 K. However, the intensity of precipitation depends not only on the ageing temperature, but also on the concentration of quenched-in vacancies, which can be strongly affected by quenching temperature. So far, ageing effects have been studied for alloy solution treated between 1070 K and 1170 K [1,2,[4][5][6][7][8][10][11][12]]. An exception is the work by Kompatscher et al [9] where the samples, with rather high Ni excess, were quenched from 1270 K and precipitation was detected even without intentional ageing of the samples.…”
mentioning
confidence: 97%
“…[10], until the precipitate size reaches approximately 1 lm [11]. These nm size precipitates efficiently suppress the transition to B19 0 martensite.…”
mentioning
confidence: 98%
See 1 more Smart Citation